K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 10 2018

      \(\frac{a}{ab}+a+1+\frac{b}{bc}+b+1+\frac{c}{ca}+c+1\)

\(=\frac{1}{b}+a+1+\frac{1}{c}+b+1+\frac{1}{c}+c+1\)

\(=3+a+b+c+\frac{1}{a}+\frac{1}{c}+\frac{1}{b}\)

\(=3+\frac{a^2+1}{a}+\frac{b^2+1}{b}+\frac{c^2+1}{c}\)

\(...............................................................\)

30 tháng 6 2018

Ta có A=\(\left(ab+bc+ca\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)-abc\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\right)\)

=\(2\left(a+b+c\right)+\frac{ab}{c}+\frac{bc}{a}+\frac{ca}{b}-\frac{ab}{c}-\frac{bc}{a}-\frac{ca}{b}=2\left(a+b+c\right)\)

30 tháng 6 2018

\(A=\left(a+b\right)\left(a^2-ab+b^2\right)+3ab\left[\left(a+b\right)^2-2ab\right]+6a^2b^2=a^2-ab+b^2+3ab\left(1-2ab\right)+6a^2b^2\)

=\(\left(a+b\right)^2-3ab+3ab-6a^2b^2+6a^2b^2=1\)

2) Ta có \(A=\left(a-1\right)\left(b-1\right)\left(c-1\right)=abc-ab-bc-ca+a+b+c-1=0\)

9 tháng 12 2015

 a/(ab+a+1) + ab/(abc+ab+a)+abc/(ab.ac+ab.c+ab.1) 
=a/(ab+a+1)+ab/(1+a+ab)+1/(a+1+ab)=tự tính đi vì chung mẫu rồi

3 tháng 4 2017

4 tháng 9 2018

\(A=\left(ab+bc+ca\right).\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)-abc.\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\right).\)

\(A=\frac{1}{b}+\frac{1}{a}+\frac{ab}{c}+\frac{bc}{a}+\frac{1}{c}+\frac{1}{b}+\frac{1}{c}+\frac{ca}{b}+\frac{1}{a}-\frac{bc}{a}-\frac{ac}{b}-\frac{ab}{c}\)

\(A=2\cdot\frac{1}{b}+2\cdot\frac{1}{a}+2\cdot\frac{1}{c}\)

\(A=2.\left(\frac{1}{b}+\frac{1}{a}+\frac{1}{c}\right)\)

4 tháng 9 2018

Đặt;\(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=m\Rightarrow mabc=ab+bc+ca\)

\(\Rightarrow m^2=\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}+2\left(\frac{1}{ab}+\frac{1}{bc}+\frac{1}{ca}\right)\)

\(\Rightarrow m^2-2\left(\frac{a+b+c}{abc}\right)=\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\)

Thay vào A=\(mabc.m-abc.\left(m^2-2\left(\frac{a+b+c}{abc}\right)\right)=m^2abc-abcm^2+2\left(a+b+c\right)\)

\(=2a+2b+2c\)

NV
20 tháng 12 2020

\(B=\left(ab+bc+ca\right)\left(\dfrac{ab+bc+ca}{abc}\right)-abc\left(\dfrac{a^2b^2+b^2c^2+c^2a^2}{a^2b^2c^2}\right)\)

\(=\dfrac{\left(ab+bc+ca\right)^2-\left(a^2b^2+b^2c^2+c^2a^2\right)}{abc}\)

\(=\dfrac{a^2b^2+b^2c^2+c^2a^2+2abc\left(a+b+c\right)-\left(a^2b^2+b^2c^2+c^2a^2\right)}{abc}\)

\(=2\left(a+b+c\right)\)